2019
DOI: 10.1186/s12884-019-2251-5
|View full text |Cite
|
Sign up to set email alerts
|

Fetal weight estimation at term – ultrasound versus clinical examination with Leopold’s manoeuvres: a prospective blinded observational study

Abstract: Background Fetal weight estimation is of key importance in the decision-making process for obstetric planning and management. The literature is inconsistent on the accuracy of measurements with either ultrasound or clinical examination, known as Leopold’s manoeuvres, shortly before term. Maternal BMI is a confounding factor because it is associated with both the fetal weight and the accuracy of fetal weight estimation. The aim of our study was to compare the accuracy of fetal weight estimation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
3
27
0
4
Order By: Relevance
“…Other studies prior to 2006 reported fetal weight estimation accuracies that varied between 23 and 78%, 6 but few of these distinguished between overestimated and underestimated group features. More recent studies from other countries have similar degrees of accuracy to ours but they have different population demographics such as lower mean maternal ages, weights and normal range BMI, 5,9 compared with our average BMI of 27kg/m 2 which is classified as overweight.…”
Section: Discussionsupporting
confidence: 62%
“…Other studies prior to 2006 reported fetal weight estimation accuracies that varied between 23 and 78%, 6 but few of these distinguished between overestimated and underestimated group features. More recent studies from other countries have similar degrees of accuracy to ours but they have different population demographics such as lower mean maternal ages, weights and normal range BMI, 5,9 compared with our average BMI of 27kg/m 2 which is classified as overweight.…”
Section: Discussionsupporting
confidence: 62%
“…Accurate prenatal estimation of birth weight is useful in the management of labour and delivery, permitting obstetricians to make decisions about instrumental vaginal delivery, trial of labour for patients suspected of having a low birth weight or macrosomic fetus (1). According to the existing literature, there is no truly accurate technique for evaluating FW (2). Before delivery, accurate estimation of FW can have a major approach for decision and management of labour, perinatal outcome can be improved better (3).…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of FW can be done by external abdominal measurements, alone or associated with fundal height measurement and/or USG scan near 32 weeks (4). Since the advent of ultrasound and its dissemination over the last three decades, and despite the lack of conclusive evidence, there has been a widespread belief that ultrasound is more accurate than other methods for predicting fetal weight (2).…”
Section: Introductionmentioning
confidence: 99%
“…EFW in late pregnancy or before delivery is often an important variable in clinical decision-making in obstetrics. Fetal weight estimation is of key importance in the decision-making process for obstetric planning and management (1).…”
Section: Introductionmentioning
confidence: 99%